RANCANG BANGUN SISTEM PEMANGGIL DARURAT PADA SITUASI PERAMPOKAN BERBASIS ANDROID - Yusuf Mufti; Nurochman Nurochman (Kaunia: Integration and Interconnection Islam and Science, 2013)
In 2012, media quite often proclaim the existence of a robbery in the various regions of the Special Region of Yogyakarta (DIY). The robberies were reported in about 222 of criminal reports until the end of November 2012 and 39 cases occured especially in bussiness offices. In robbery situation, the victims will panic commonly and may be under a pressure so they are difficult to ask for help using normal communication. The system was built to help the victims to request assistance through their Android devices immediately. The system is capable of transmitting data into server at the police station through internet and send SMS to police’s cellular phone by pressing a shortcut. The system works by utilizing the GPS signal. The system has been tested by a number of respondents with good results.